Comparison of Altman Z-Score Model and Springate Model in Predicting Financial Distress: Case Study of FMCG Companies in Indonesia - Dailami, Ahmad; Erifianto, Mochamad Kardofa (International Journal of Quantitative Research and Modeling, 2024)
Financial distress is a serious threat to the sustainability of a company. This study aims to evaluate the ability of the Altman Z-Score model and the Springate model in predicting the possibility of financial distress in FMCG companies. By comparing the performance of the two methods, this study is expected to provide recommendations for the most appropriate method to use in monitoring the company's financial health. The results of this study have important implications for investors, creditors, and company management in making investment and risk management decisions.